Semantic Multimedia First International Conference on Semantics and Digital Media Technologies, SAMT 2006, Athens, Greece, December 6-8, 2006. Proceedings - Avrithis, Yannis; Kompatsiaris, Yiannis; Staab, Steffen; O$1 (BConnor, Noel E.s; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
We are delighted to welcome you to the proceedings of the 1st International Conference on Semantic and Digital Media Technologies held in Athens. SAMT 2006 aims to narrowthe large disparity between the low-level descr- tors that can be computed automatically from multimedia content and the ri- ness and subjectivity of semantics in user queries and human interpretations of audiovisual media $1 (BThe Semantic Gap. SAMT started out as two workshops, EWIMT 2004 and EWIMT 2005, that quickly achieved success in attracting high-quality papers from across Europe and beyond. This year EWIMT turned into the full-?edged conference SAMT, bringing together forums, projects, - stitutions and individuals investigating the integration of knowledge, semantics and low-level multimedia processing, and linking them with industrial engineers who exploit the underlying emerging technology. In total, 68 papers were submitted to the SAMT 2006 conference and each was reviewed by at least two independent reviewers. We are grateful to the membersoftheTechnicalProgramCommitteewhocompletedthesereviewsand allowed us to put together a very strong technical program of 17 papers. The selection process was very competitive with only 25% of papers being selected for oral presentation. The program also included two invited keynote talks from Alan Smeaton and Guus Schreiber, and we are very grateful to them for their insightful presentations.s
Content vs. Context for Multimedia Semantics: The Case of SenseCam Image Structuring -- A Scalable Framework for Multimedia Knowledge Management -- In Search for Your Own Virtual Individual -- Enabling Multimedia Metadata Interoperability by Defining Formal Semantics of MPEG-7 Profiles -- Trend Detection in Folksonomies -- Personal Semantic Indexation of Images Using Textual Annotations -- Human Activity Language: Grounding Concepts with a Linguistic Framework -- An Engine for Content-Aware On-Line Video Adaptation -- Image Clustering Using Multimodal Keywords -- A Probability-Based Unified 3D Shape Search -- A Bayesian Network Approach to Multi-feature Based Image Retrieval -- Extraction of Motion Activity from Scalable-Coded Video Sequences -- Image Classification Using an Ant Colony Optimization Approach -- Use of Image Regions in Context-Adaptive Image Classification -- BPT Enhancement Based on Syntactic and Semantic Criteria -- Semantic Image Analysis Using a Learning Approach and Spatial Context -- A Context-Based Region Labeling Approach for Semantic Image Segmentation -- Automated Speech and Audio Analysis for Semantic Access to Multimedia.
Keywords: Popular works; Computer communication systems; Data mining; Multimedia information systems; Text processing (Computer science).; Computer science; Popular Science; Popular Computer Science; Multimedia Information Systems; Computer Communication Networks; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Document Preparation and Text Processing; Electronic books